Potential protein and biodiesel sources from black soldier fly larvae : insights of larval harvesting instar and fermented feeding medium - Wong, Chung Yiin; Siti Suhailah, Rosli; Uemura, Yoshimitsu; Ho, Yeek Chia; Leejeerajumnean, Arunsri; Kiatkittipong, Worapon; Cheng, C. K.; Lam, Man Kee; Lim, Jun Wei (MDPI AG, 2019)
Primarily produced via transesterification of lipid sources, fatty acid methyl ester (FAME) of biodiesel derived from insect larvae has gained momentum in a great deal of research done over other types of feedstock. From the self-harvesting nature of black soldier fly larvae (BSFL), research had, however, only concentrated on the harvest of BSFL on sixth instar. Through rearing BSFL on coconut endosperm waste (CEW), 100 BSFL were harvested at the fifth and sixth instar, then modification on CEW with mixed-bacteria powder was carried out. It was found that the fifth instar BSFL had 34% lipid content, which was 8% more than the sixth instar. Both instars had similar corrected protein contents around 35–38%. The sixth instar BSFL contained around 19% of chitin, which was about 11% more than the fifth instar. Biodiesel products from both instars showed no differences in terms of FAME content. With modification on CEW, at 0.5 wt% of mixed-bacteria powder concentration, the maximum waste-to-biomass conversion (WBC) and protein conversion (PC) were achieved at 9% and 60%, respectively. Moreover, even with the shorter fermentation time frame of CEW, it did not affect the development of BSFL in terms of its WBC and PC when fed with 14 and 21 days fermented medium. FAME from all groups set, which predominantly constituted about C12:0 at around 60%, followed by C14:0 at around 15%, C16:0, and C18:1 both at 10% on average. Lastly, the FAME yield from BSFL was improved from 25% (sixth instar) to 33% (fifth instar) and showed its highest at 38.5% with modification on raw CEW with 0.5 wt% mixed-bacteria powder and fermented for 21 days. Thus, harvesting BSFL at earlier instar is more beneficial and practical, as it improves the FAME yield from the BSFL biomass.